Dynamic Compression Properties of the Resistance Spot Welding of High Strength Steels under Varying Temperature Conditions. (26th August 2021) - Fan, Chunlei; Wang, Huanran; Ma, Dongfang
Abstract : In this paper, we have studied the dynamic compression performance of the RSW of QP980 steel and TRIP800 steel by using a split Hopkinson pressure bar (SHPB), and we have also examined the fracture mode of the two research objects. It is found that the spot welding zone is primarily composed of the martensite structure, and there is a sparse defect of crystal structure adjacent to the center of nugget. In addition, there are evident gaps between the plates on both sides of the spot welding zone. Through the measurement of the microhardness of the two grade steel, it is found that the average hardness of the RSW of QP980 steel is higher than that of TRIP800 steel. There is a softening region in the interface of the heat affected zone and the substrate zone. The dynamic compression experiments are carried out on the RSW of QP980 steel and TRIP800 steel under 200°C and 300°C conditions, and it is found that the strain rate would increase with the rising temperature, but the compressive strength would experience declines. Furthermore, the sparse defects of crystal structure adjacent to the center of nugget would lead to stress rebound when the specimen is compressed. Moreover, through the observation of the fracture surface of the recovered specimens, it is found that the fracture of the nugget is brittle, whereas the fracture mode of the sample is more complicated. In addition, the fracture surface features a number of "river pattern" cleavage facets, and there are very few dimples of ductile tearing. This study is expected to have huge implications to the safety of vehicle body under high-speed impact.